Effect of transporter inhibitors on paraquat resistance of horseweed (Conyza canadensis /L./ Cronq.) - Halász, Krisztián (Acta Biologica Szegediensis, 2002)
A paraquat inducible protein is supposed to play a role in the resistance of horseweed Conyza canadensis (L.) Cronq., which presumably functions by carrying paraquatto a metabolically inactive compartment. Here we studied the effect of transporter inhibitors (CCCP, DCCD, TP P an d vanadate ) on the decrease of functional activity caused by paraquat in order to reveal the possible roles of different types of transporters in the resistance mechanism. Results presented here imply the participation of not directly energized antiporters in paraquatsequestration.